The 60s Turnaround as a Test on the Causal Relationship between Sociability and Happiness - Leonardo Becchetti; Elena Giachin Ricca; Alessandra Pelloni (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
The nexus between social leisure and life satisfaction is riddled with endogeneity problems. In investigating the causal relationship going from the first to the second variable we start from considering that retirement is an event after which the time investable in (the outside job) relational life increases. We instrument social leisure with the probability of retirement of the three and four years younger cohorts. With such approach we document that social leisure has a positive and significant effect on life satisfaction. Our findings shed some light on the age-happiness pattern. Policy implications are also discussed.
Keywords: I30; D61; A11; A13; 330; Life satisfaction; relational goods; social capital